AB0116 Treatment of systemic sclerosis with anti-tnf-alpha antibodies. a case report. (1st June 2001) - Welcker, M; Hollatz, R; Werling, A; Emmlinger, M; Franck, H
Abstract : Background: In february 1999 a 39 year old woman developed progressive swelling of the hands, arthralgias, Raynaud's phenomenon, dyspepsia and reduced physical strength. For this reasons, positive ANA's (no anti topoisomerase I antibodies, pathologic oesophagus manometry and clinical signs of lung involvement including typical skin lesions (thickening, necrosis, erythema anulare, etc.) systemic sceloris was diagnosed. In the course of disease DMARDs such as penicillamin and cyclophosphamide showed no efficacy over a period of 18 months. Relatively high doses of methylprednisolone (up to 250 mg/d; not below 20 mg/d) were needed to reduce the clinical signs of the disease. In december 2000 anti-TNF-alpha-antibody therapy (infliximad) was started in a dosage of about 5 mg per kg body weight. After four perfusions (weeks 0, 2, 6, 10) clinical improvement (healing of skin necrosis, reduced dyspepsia and dyspnoe, increased general feeling, reduced VAS from 80 to 20, increased opening of the mouth, increased movement of the hands and fingers) permitted a slow reduction of the daily steroid dose. Objectives: ./. Methods: ./. Results: ./. Conclusion: This is a case with positive therapeutic onset of infliximab (remicade) in a case with systemic sclerosis.